Optical energy of spherical velocity with optical magnetic density in Heisenberg sphere space S2Heis3 - Korpinar, Talat; Korpinar, Zeliha; Yeneroglu, Mustafa (Elsevier Gmbh, 2021)
In this article, we define a new concept of spherical optical magnetic density with biharmonic particles in spherical Heisenberg space. Moreover, we construct the optical energy of spherical tangent magnetic biharmonic particles and new Lorentz fields. Furthermore, we show that optical energy and optical magnetic flux density can be stated by Frenet fields in Heisenberg space.
Keywords: Bienergy; Optical spherical geometric energy; Spherical Heisenberg space; Magnetic field; Symmetries